Electromechanical device for temperature control of internal combustion engines - Mamani Torres, Marco Antonio (2019)
Internal combustion engines are the most commonly used engines in the automotive world. However, these engines lack an overheating prevention system against cooling system failures when they exceed their normal operating temperature. Less experienced drivers (users) usually do not notice overheating until the engine stops, generating economic expenses in engine repairs. As such, this paper describes the design and construction of an electromechanical device to prevent engine overheating. This device is installed in a vehicle and operates independently from the electronic control unit (ECU); it records the coolant temperature and controls air admission to the engine of the vehicle in which it is installed. In addition, a new Arduino-based card will receive signals from a temperature sensor as input and process them according to its programming. Then, it will send signal outputs to the actuators: a servomotor, monitor, LED display, and buzzer. To control the intake flow, a butterfly valve is used with the servomotor. This valve partially or totally restricts the engine airflow, based on the temperature programmed for the Arduino, thus protecting the engine from overheating.